The use of intravitreal ranibizumab to treat neovascular glaucoma because of retinal amyloid angiopathy in familial amyloidosis transthyretin V30M related - Beirão, N.M. (2014)
Purpose: The purpose of this study to report a patient with amyloidotic angiopathy and neovascular glaucoma who was treated with intravitreal injection of ranibizumab followed by laser photocoagulation. Methods: A 52-year-old liver-transplanted woman with familial amyloidotic polyneuropathy presented with unilateral rubeosis iridis and neovascular glaucoma. A complete ocular examination and fluorescein and indocyanine green angiography were performed. Results: Best-corrected visual acuity before injection was 0.05 (Snellen) in the left eye, and intraocular pressure was 42 mmHg. Fluorescein angiography showed vascular occlusion in the retinal periphery, focal staining of vessels, and microaneurysms. Indocyanine green angiography showed hyperfluorescent spots alongside the choroidal veins. Two days after receiving intravitreal injection of ranibizumab, the clinical picture regressed. The diagnosis of retinal amyloid angiopathy was made, and a peripheral retinal laser photocoagulation was done. The final best-corrected visual acuity after 2 years of follow-up was 0.4 (Snellen) in the left eye. Conclusion: Intravitreal injections of ranibizumab should be evaluated for a potential role on the treatment of amyloid angiopathy neovascular glaucoma. Careful retinal periphery examination should be included in the ophthalmologic examination of all familial amyloidotic polyneuropathy patients.